Zilebesiran, an RNA Interference Therapeutic Agent for Hypertension - Desai, Akshay S.; Webb, David J.; Taubel, Jorg; Casey, Sarah; Cheng, Yansong; Robbie, Gabriel J.; Foster, Don; Huang, Stephen A.; Rhyee, Sean; Sweetser, Marianne T.; Bakris, George L. (The New England journal of medicine, 2023)
In this phase 1 study involving persons with hypertension, zilebesiran (an RNA interference therapeutic agent) was associated with decreases in angiotensin levels and systolic and diastolic blood pressure.